2022
DOI: 10.1073/pnas.2108672119
|View full text |Cite|
|
Sign up to set email alerts
|

Identification of genetic risk loci and prioritization of genes and pathways for myasthenia gravis: a genome-wide association study

Abstract: Myasthenia gravis is a chronic autoimmune disease characterized by autoantibody-mediated interference of signal transmission across the neuromuscular junction. We performed a genome-wide association study (GWAS) involving 1,873 patients diagnosed with acetylcholine receptor antibody-positive myasthenia gravis and 36,370 healthy individuals to identify disease-associated genetic risk loci. Replication of the discovered loci was attempted in an independent cohort from the UK Biobank. We also performed a transcri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…The second protective trait is a higher proportion of CD4 + Tregs, which is in accordance with previous studies. Previous GWASs on MG have identified the correlations between variants in genes (e.g., CTLA4 and PTPN22) with MG risk, which directly modulates the proportion or function of CD4 + Tregs ( 9 , 11 ). Biological evidence from experimental autoimmune MG (EAMG) models has explained the potential mechanisms in which CD4 + Tregs suppressed the abnormal proliferation of T effector cells in response to MG-related antigens ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The second protective trait is a higher proportion of CD4 + Tregs, which is in accordance with previous studies. Previous GWASs on MG have identified the correlations between variants in genes (e.g., CTLA4 and PTPN22) with MG risk, which directly modulates the proportion or function of CD4 + Tregs ( 9 , 11 ). Biological evidence from experimental autoimmune MG (EAMG) models has explained the potential mechanisms in which CD4 + Tregs suppressed the abnormal proliferation of T effector cells in response to MG-related antigens ( 31 , 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…These T-cell traits included subtypes in the T-cell panel (double negative, double positive, CD4 + , CD8 + ), regulatory T (Treg) panel, maturation stages (central memory/effector memory/terminally differentiated), and cell marker expression levels on different T cells. As a primary analysis, the MG data were sourced from the currently largest meta-GWAS conducted in the US and Italy (1,873 patients versus 36,370 age/gender-matched controls) ( 11 ). Only anti-acetylcholine receptor antibody-positive (AChR+) MG patients were enrolled in this study, and patients with positive test results for antibodies to muscle-specific kinase (MuSK+) were excluded from the enrollment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we have proposed a strategic framework that generalizes how to establish the link from genetic loci to modulated genes that can be further linked to drug targets ( 14 , 15 ). Our advocates of genetic target prioritization have driven this field of research ( 16 22 ). In this study, we extended this into genomics-led target prioritization (called ‘ END’ ) and demonstrated better performance than the status quo approaches ( Figure 1 ), with the aim of providing genomic evidence for endometriosis as an inflammatory systemic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Priority index or Pi, a genetics-led target prioritisation approach ( 5 ), has already supported specific applications for a wide range of diseases, including but not limited to: Alzheimer's disease ( 15 ), Dupuytren's disease ( 16 ), endometriosis ( 17 ), kidney stone disease ( 18 ), myasthenia gravis ( 19 ) and type 1 diabetes ( 20 ). The Pi approach is unique in three ways.…”
Section: Introductionmentioning
confidence: 99%